APPLICATION OF STUDENT TEAMS ACHIEVEMENT DIVISION COOPERATIVE MODEL - Damayanti, Eva; Marasabessy, Fachria Y. (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Terbuka, 2023)
This study aims to determine the effectiveness of applying the Student Teams Achievement Division (STAD) Cooperative learning method in improving the English language achievement of class X students at SMA Muhammadiyah 3 Bancar Tuban. This study used a classroom action research approach, in which the researcher acted as a teacher and applied both methods for four weeks. The study participants consisted of 22 students who were divided into several groups. Data were collected through pre-test and post-test, observation, and interviews. The results of the study show that through the application of the STAD model, students become active in groups, students work together with other students, students can also master the lessons delivered, and students help each other when friends in the group experience learning difficulties. This can all be seen in the results of observations of students in class during the learning process. So it can be concluded that the application of the cooperative model type Student Teams Achievement Division (STAD) can increase student understanding and achievement.